Understanding transitioning from traditional business analysis to agile business analysis: the case of South African Banks - Iyamu, Augustine (Department of Information Systems, 2025)
Customer needs are rapidly changing, and organisations strive to respond accordingly. Thus, many organisations explore innovative approaches to address their needs and challenges. Some innovations include developing new technologies, products, and service offerings. These innovative approaches need organisations to inspect, adapt and adopt new ways of working and moving (transitioning) from the traditional business analysis approach to the agile one. However, the transition has its challenges. Some challenges are either unknown or unclear to many organisations that intend to transition from a traditional business analysis approach to an agile one. Some of the challenges organisations faced are struggling to reduce uncertainty, and lack of quicker response time. This has been attributed to a lack of empirical evidence or limited terms of reference. This was the main motivation for this study. This study aimed to help gain a deeper understanding of transitioning from traditional business analysis to agile business analysis in the context of large South African organisations. Qualitative research methods were employed to achieve this aim. Two financial services (banking) organisations were selected as cases using the case study method. This allows activities to be understood in their natural settings and from two perspectives. The use of two cases helped with the generalisation of some of the findings. Participants were selected from both organisations based on the criteria. The semi-structured interview technique was used to gather data to a point where new information was not forthcoming. The moments of translation from the Actor Network Theory (ANT) were used to analyse the data collected. Primarily, this is because ANT focuses on relationships, interactions between actors, and how negotiations shift from one point to another. Thus, the theory was crucial in achieving the aim of the study. Using the theory for analysis helps reveal the benefits and challenges of transitioning from a traditional approach to agile business analysis. This includes the interactions between human and non-human actors, leading to transition. Furthermore, the findings were interpreted to understand better how the factors influence transitioning from a traditional business analysis approach to an agile business analysis in both organisations. The study provides insights into the challenges and benefits of transitioning from traditional business analysis to an agile approach. The challenges emanate from various factors. For example, change to resistance and lack of understanding of lean requirements documentation in organisations. This is attributed to business analysts still using traditional business analysis mindset, advancement of individual analysis approach within the teams, lack of buy-in and support from business stakeholders and senior management to ensure quicker delivery, and unclear roles and responsibilities within teams, etc. and also the study highlighted various benefits associated with transitioning to agile business analysis which include improved collaborations that encourage the team to function as a unit, improved visibility and transparency within teams, increase productivity and quicker time to market of the organisation's product and services. Despite the comprehensiveness of the study, there were limitations, which are highlighted. Additionally, based on the findings and interpretation, a conclusion was drawn that there is a need for further research. Thus, areas of further are proposed. The study made contributions from theoretical and practical standpoints. Theoretically, the study contributes by adding to the existing literature in the areas of business process and project methodological approach from both academic and business perspectives. Additionally, it advances the use of actor-network theory as a lens in information systems research. Practically, the findings from the study can be used to guide policy and strategy development on the implementation of agile business analysis in an organisation.